2020
DOI: 10.1101/2020.11.11.377630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to Airborne Bacteria Depends upon Vertical Stratification and Vegetation Complexity

Abstract: Exposure to biodiverse aerobiomes may support human health, but it is unclear which ecological factors influence exposure. Few studies have investigated near-surface green space aerobiome dynamics, and no studies have investigated aerobiome vertical stratification in different green spaces. We used columnar sampling and next generation sequencing of the bacterial 16S rRNA gene, combined with geospatial and network analyses to investigate aerobiome spatio-compositional dynamics. We show a strong effect of habit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 73 publications
(99 reference statements)
0
17
0
Order By: Relevance
“…Moreover, some researchers are assessing whether restoration interventions and aspects of habitat complexity can improve the aerobiome (microbiome of the air) with potential human health implications (Breed et al, 2021;Robinson et al, 2020;Robinson et al, 2021). Drones could potentially help facilitate the collection of airborne eDNA samples in different restoration settings.…”
Section: Air Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some researchers are assessing whether restoration interventions and aspects of habitat complexity can improve the aerobiome (microbiome of the air) with potential human health implications (Breed et al, 2021;Robinson et al, 2020;Robinson et al, 2021). Drones could potentially help facilitate the collection of airborne eDNA samples in different restoration settings.…”
Section: Air Quality Assessmentmentioning
confidence: 99%
“…Indeed, collecting airborne eDNA samples is an emerging area of research in ecology, for example, for monitoring terrestrial vertebrate communities (Lynggaard et al, 2022). Moreover, some researchers are assessing whether restoration interventions and aspects of habitat complexity can improve the aerobiome (microbiome of the air) with potential human health implications (Breed et al, 2021; Robinson et al, 2020; Robinson et al, 2021). Drones could potentially help facilitate the collection of airborne eDNA samples in different restoration settings.…”
Section: Restoration Monitoringmentioning
confidence: 99%
“…This hypothesis proposed that a failure of immunoregulation and associated health problems (e.g., mental health conditions) in modern Western environments ( 83 ), indicated by a balanced expansion of effector T-cell populations and regulatory T cells (Treg), is due to reduced exposures to microorganisms with which humans coevolved, including: (i) pathogens associated with the “old infections” that were present throughout life in evolving human hunter-gatherer populations ( 114 ); (ii) the commensal microbiota, which have been altered by the modern Western lifestyle, including a diet that is frequently low in microbiota-accessible carbohydrates ( 115 117 ); and (iii) organisms from the natural environment with which humans were in daily contact with (and, consequently, had to be tolerated by the immune system) ( 83 ). More recently, the observation that two major socioecological trends (i.e., the loss of biodiversity, and increasing incidence of inflammatory diseases) are interdependent led to the biodiversity hypothesis ( 67 , 99 , 100 ). This states that people’s reduced contact with nature and environmental biodiversity has altered the human commensal microbiota’s capacity to induce immunoregulation and to prevent inappropriate inflammation as well as associated negative health outcomes ( 7 , 89 , 118 ).…”
Section: Human Psychology and Mental Healthmentioning
confidence: 99%
“…Recently, it was shown that urban green space aerobiomes are vertically stratified, with an altitudinal decay in bacterial alpha diversity, and possibly a higher relative abundance of pathogenic taxa at higher altitudes (Robinson et al 2020a). This reflects a transition from local plant and soil-related microbiomes at low heights into a broader urban (typically non-green space) airshed (Robinson et al 2020b). A potential mitigation measure for this could be to augment vertical planting in urban areas, allowing exposure to higher natural microbial alpha diversity in the vertical dimension (Fig.…”
Section: Vegetation Microbiomes and The Built Environmentmentioning
confidence: 99%
“…Evidence has shown that degraded habitats may harbour a greater relative abundance and diversity of opportunistic human pathogens, and ecological restoration may restore health-regulating assemblages (Liddicoat et al 2019;Robinson et al 2020a). Moreover, microbial exposure in urban green/blue spaces could improve our health but may depend heavily upon environmental and design factors including vertical stratification (layering of microbes in the near-surface atmosphere), vegetation presence, complexity and management (Robinson et al 2020b;Roslund et al 2020), airflow, and soil management.…”
Section: Introductionmentioning
confidence: 99%